Comparison of Intravenous Regional Anesthesia with Single-Cuff Forearm Tourniquet and Hematoma Block and Traditional Method in Patients with Distal Radius Fractures; A Randomized Clinical Trial - Arash Farbood; Saeed Khademi; Ramin Tajvidi; Minoo Hooshangi; Saeed Salari; Mandana Ghani; Sakineh Tahmasebi; Hamid Jamali (Bulletin of Emergency and Trauma, 2020)
Objective: To investigate the effect of intravenous regional anesthesia with single-cuff forearm tourniquet and hematoma block on intraoperative and postoperative pain intensity of patients with distal radial bone fracture. Methods: In this randomized clinical trial, a total number of 52 patients with distal radius fractures were randomly assigned to receive either a traditional Bier block with 3 mg.kg-1 lidocaine (D group) or a single-cuff forearm tourniquet intravenous regional anesthesia with 1.5 mg.kg-1 lidocaine and a hematoma block with 10 mL 0.5% bupivacaine (S group). Pain intensity score of numerical rating scale (NRS) was measured hourly for 6 hours, then every two hours till 12th hour and every 4 hours until 24th postoperative hour. Total morphine consumption in the first 24 hours after surgery, its side effects and the patients’ global satisfaction were assessed in each group. Results: Mean total morphine consumption during the first 24 hours after surgery was 11.68±7.88 mg in group D and 7.12±4.42 mg in group S (p=0.13). Pain intensity score of NRS both during recovery room and surgical ward stay was less in S group compared to D group (0.016 and 0.02, respectively). Conclusion: Intravenous regional anesthesia with single cuff forearm tourniquet and hematoma block compared to the traditional Bier block reduced intraoperative and postoperative pain intensity more effectively in patients with distal fracture of the radius bone and also reduced morphine consumption during the first 24 hours after surgery. Clinical Trial Registry: IRCT201604223213N4